Assessment of the Genetic Diversity of Groundnut (Arachis hypogaea L.) Using SSR Markers - Rathava, Rajeshvari I.; Chandramohan, Sangh; Gajera, H. P.; Bhatt, S. B.; Shitap, M. S. (International Journal of Bio-resource and Stress Management, 2025)
The experiment was conducted during the kharif-2021 season (June–October, 2021) at the ICAR-Directorate of Groundnut Research, Junagadh, Gujarat, India, to assess genetic diversity in groundnut (Arachis hypogaea L.) using Simple Sequence Repeat (SSR) markers. The study revealed significant genetic variation, which was crucial for effective breeding and conservation strategies. Across markers, 2 to 10 alleles were identified, with an average of 4.63 alleles per marker, indicating a broad genetic base. Among the genotypes, DGR_D1 exhibited the highest genetic diversity (0.8425) and Shannon information index (1.983), making it valuable for enhancing variability in breeding programs. In contrast, DGR_D73 showed the lowest diversity (0.1017) but recorded the highest major allele frequency (0.9462), indicating limited variability. Heterozygosity ranged from 0 to 1, with DGR_D46 achieving the maximum observed heterozygosity (1.0), reflecting its genetic uniqueness.Regional analysis revealed significant patterns of genetic differentiation. Punjab and Haryana exhibited the greatest differentiation, suggesting high variability between these regions, while Maharashtra and Tamil Nadu populations were genetically similar, reflecting limited regional variation. These findings underscored the effectiveness of SSR markers in assessing genetic diversity and guiding breeding efforts. By identifying genetically diverse genotypes and understanding regional variations, the study provided a foundation for targeted breeding programs, conservation strategies, and the improvement of groundnut resilience, ultimately contributing to enhanced productivity and sustainable cultivation.